Advanced Applications of Artificial Intelligent Systems in Civil Engineering: A Review. Issue 1 (July 2021) - Kate, Shrikant; Swami, Vidula; Doiphode, Sanjay; Singh, Vijay
Abstract: Artificial Intelligence (AI) focuses on smart machines and their architecture and application. Solutions to complex systems need large computing resources, but AI-based technologies may provide simpler alternative solutions. As a result, the use of AI has grown in a variety of technological fields in recent years in general and has extended to civil engineering in particular. Civil engineering, on the other hand, has not yet been extensively investigated using AI techniques. To fill in the gap, this paper explores, how artificial intelligence has been used and developed in civil engineering in recent years, including Machine Learning Techniques, with the advancement of machine learning techniques in recent years, big data and deep learning developments have been successfully implemented in numerous fields of civil engineering. The research direction and challenges of artificial intelligence in civil engineering over the last few years can be learned through the work of this paper. This paper discusses the use of artificial intelligence technologies in civil engineering, including machine learning techniques, smart algorithms, big data, and deep learning.